Why Coaching Turns Directive: Identity Threat and Double-Loop Learning in Coaching Interactions - Iwan Pramana; Indria Handoko (Fundamental and Applied Management Journal, 2026)
Coaching is widely understood as a non-directive approach. Coaching is aimed at developing individual thinking capacity and autonomy. However, coaching interactions in practice often shift toward directive behaviors. A phenomenon referred to as directive drift. This paper develops a conceptual model to explain why coaching turns directive.  The model integrates identity threat, role conflict, and perceived social expectation within coaching interactions. The model proposes that when coachees explicitly or implicitly expect direct answers, leaders experience perceived social pressure. This pressure triggers identity threat related to their role as competent experts. This threat intensifies role conflict between functioning as a non-directive coach and a directive problem-solver. As a result, leaders are more likely to engage in directive behaviors such as advice-giving. Such behaviors may provide short-term relief for both the leader and the coachee. However, they risk undermining long-term autonomy and problem-solving capability. As a theoretical contribution, this paper introduces double-loop learning as a reflective mechanism. This mechanism can interrupt directive drift. By examining underlying assumptions about leadership identity and the need to provide answers, leaders can sustain non-directive coaching practices. This study reframes directive behavior. It is not merely a skill deficit. Instead, it is an identity-driven response shaped by social expectations. The paper also proposes a process model. This model explains both the emergence and mitigation of directive drift.